First external description of the female of Stygioides italica Mazzei & Yakovlev, 2016 (Lepidoptera: Cossidae) - Pinzari, M.; Pinzari, M. (SHILAP Revista de lepidopterología, 2020)
The female of Stygioides italica Mazzei & Yakovlev, 2016 is described for the first time.